A Basal Chordate Model for Studies of Gut Microbial Immune Interactions - Dishaw, Larry J.; Flores-Torres, Jaime A.; Mueller, M. Gail; Karrer, Charlotte; Skapura, Diana P.; Melillo, Daniela; Zucchetti, Ivana; De Santis, Rosaria; Pinto, Maria Rosaria; Litman, Gary W. (Frontiers in Immunology, 2012)
Complex symbiotic interactions at the surface of host epithelia govern most encounters between host and microbe. The epithelium of the gut is a physiologically ancient structure that is comprised of a single layer of cells and is thought to possess fully developed immunological capabilities. Ciona intestinalis (sea squirt), which is a descendant of the last common ancestor of all vertebrates, is a potentially valuable model for studying barrier defenses and gut microbial immune interactions. A variety of innate immunological phenomena have been well characterized in Ciona, of which many are active in the gut tissues. Interactions with gut microbiota likely involve surface epithelium, secreted immune molecules including variable region-containing chitin-binding proteins, and hemocytes from a densely populated laminar tissue space. The microbial composition of representative gut luminal contents has been characterized by molecular screening and a potentially relevant, reproducible, dysbiosis can be induced via starvation. The dialog between host and microbe in the gut can be investigated in Ciona against the background of a competent innate immune system and in the absence of the integral elements and processes that are characteristic of vertebrate adaptive immunity.